Hubungan Kualitas Mikrobiologis Air Sumur Gali dan Pengelolaan Sampah di Rumah Tangga dengan Kejadian Diare pada Keluarga di Kelurahan Terjun Kecamatan Medan Marelan Tahun 2013 - marina aprina; Evi Naria; Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2014)
Correlation the quality of  microbiological dug well water and management of domestic waste with the incidence of diarrhea at  family in Terjun Village District Marelan 2013. The source of clean water which is mostly used by society is dug well. Dug well is easily contaminated by bacterial from the source of pollution. It can cause the disease like diarrhea. Moreover, waste is the source of disease too and the breeding ground of vector like fly.The purpose of this research was to know correlation between the quality of microbiological water of dug well and description management of domestic waste with the incidence of diarrhea at family in Terjun Village District Marelan.This research used the cross sectional design, to know how the correlation the quality of  microbiological water of dug well with the incidence of diarrhea and description management of domestic waste. This population are family in environment 20. And do the examination of dug well  water in respondent’s house with taking sampel by purposive sampling.The Result showed that the quality of microbiological water  of  dug well are  the  Total of uneligible coliform is 73,30% of water samples  and the uneligible Escherichia coli is 90% of water samples.  All family (100%) do not seperation the waste, all family do not provide the eligible trash, method  of  waste destruction that good is 83,30% and not good  is 16,70%. Diarrhea happened in every member family is 33,30%. There is no corellation between  the quality of the microbiological water with the incidence of diarrhea (p=1,000) and (p=0,251). Puskesmas should be made the socialization to use the water  filter and the water sanitation. The society provide the eligible  trash, do separation the waste, and keep healthy behavior of  use the water. Keywords: the quality of microbiological water, management of waste, diarrhea